2019
DOI: 10.1080/21691401.2019.1648285
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DLEU1 aggravates osteosarcoma carcinogenesis via regulating the miR-671-5p/DDX5 axis

Abstract: Long non-coding RNAs (LncRNAs) have been proven to be involved in the progression of osteosarcoma. LncRNA DLEU1 was found to act as an oncogene in various types of cancer. In this study, we aimed to explore the biological functions of DLEU1 in osteosarcoma and the specific mechanism. Our results showed that DLEU1 was highly expressed in osteosarcoma tissue specimens and cells. Downregulation of DLEU1 in osteosarcoma cells inhibited the cell proliferation, migration and invasion. Further mechanistic analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
(31 reference statements)
4
17
0
Order By: Relevance
“…Moreover, recent reports had demonstrated that knockdown of lncRNA DLEU1 significantly inhibited the invasion and migration abilities on osteosarcoma cells and glioma cells (Chen X. et al, 2019;Feng et al, 2019). Correspondingly, we found similar results that knockdown of lncRNA DLEU1 significantly inhibited the invasion and migration abilities not only in U87 cell but also in U251 cell.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, recent reports had demonstrated that knockdown of lncRNA DLEU1 significantly inhibited the invasion and migration abilities on osteosarcoma cells and glioma cells (Chen X. et al, 2019;Feng et al, 2019). Correspondingly, we found similar results that knockdown of lncRNA DLEU1 significantly inhibited the invasion and migration abilities not only in U87 cell but also in U251 cell.…”
Section: Discussionsupporting
confidence: 88%
“…Based on RNA-seq data from TCGA, we demonstrated that the differential expression gene in glioma, named lncRNA deleted in lymphocytic leukemia 1 (lncRNA DLEU1), was dramatically associated with a poor prognosis. Emerging research has reported that lncRNA DLEU1 performed an indispensable role in the genesis and progression of various tumors such as gastric cancer, osteosarcoma, pancreatic ductal adenocarcinoma, non-small cell lung cancer, and breast cancer, as well as resistance to chemotherapy in tumors (Li X. et al, 2018;Chen X. et al, 2019;Gao et al, 2019;Zhang et al, 2019;Wang C. et al, 2019;Li Y. et al, 2019). However, the progression and TMZ chemosensitivity of lncRNA DLEU1 in glioma are still vague.…”
Section: Introductionmentioning
confidence: 99%
“…DLEU1 has also been reported to be involved in the prognosis of several tumors. In osteosarcoma, DLEU1 is upregulated in tumor tissues, and CCK-8 experiments revealed that DLEU1 promotes cell proliferation ( Chen X. et al, 2019 ). Colorectal cancer patients with high DLEU1 expression have a low survival rate and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since DLEU1 was reported to serve as a competitive endogenous RNA (ceRNA) at the post-transcriptional level in various diseases (Chen et al 2019 ; Feng et al 2019 ; Li et al 2020b ), we aimed to explore whether DLEU1 can serve as a ceRNA in neuropathic pain. Initially, RNA FISH was utilized to detect the subcellular localization of DLEU1 in rat microglial cells, and the results manifested that DLEU1 was primarily located in the cytoplasm of microglial cells (Fig.…”
Section: Resultsmentioning
confidence: 99%